1992
DOI: 10.1091/mbc.3.7.789
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Saccharomyces Golgi complex through the cell cycle by immunoelectron microscopy.

Abstract: The membrane compartments responsible for Golgi functions in wild-type Saccharomyces cerevisiae were identified and characterized by immunoelectron microscopy. Using improved fixation methods, Golgi compartments were identified by labeling with antibodies specific for alpha 1-6 mannose linkages, the Sec7 protein, or the Ypt1 protein. The compartments labeled by each of these antibodies appear as disk-like structures that are apparently surrounded by small vesicles. Yeast Golgi typically are seen as single, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
221
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(237 citation statements)
references
References 66 publications
14
221
0
Order By: Relevance
“…A typical Golgi element in a wild-type strain has the appearance of a curved tubular network structure, sometimes forming a complete circle (Preuss et al, 1992;Rambourg et al, 2001). In the control strain labeled with anti-HA antibodies, typical Golgi structures were observed ( Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…A typical Golgi element in a wild-type strain has the appearance of a curved tubular network structure, sometimes forming a complete circle (Preuss et al, 1992;Rambourg et al, 2001). In the control strain labeled with anti-HA antibodies, typical Golgi structures were observed ( Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…The most striking difference is the physical separation of the Golgi apparatus and the ER exit sites in mammals. In yeast the distances are very small because of the small size of the cell and the fact that there are multiple dispersed Golgi throughout the cell cytoplasm (Preuss et al, 1992). Vesicles budding from the ER are never far from a Golgi.…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known about the spatial distribution of the early secretory compartments. It was reported that the Golgi apparatus also localized close to the bud site in S. cerevisiae (Preuss et al, 1992). Similarly, Bevis et al, 2002 have suggested that the Golgi elements in Pichia pastoris might preferentially localize toward the budding site.…”
Section: Introductionmentioning
confidence: 88%
“…Most published work on the involvement of protein secretion during polarity establishment has centered on targeting, localization, and delivery of post-Golgi vesicles. For example, it was shown that the early buds of the budding yeast Saccharomyces cerevisiae contain numerous secretory vesicles that are rarely observed in the mother cell (Preuss et al, 1992). Such polarized distribution depends on intact actin cables and type V myosins (Johnston et al, 1991;Govindan et al, 1995).…”
mentioning
confidence: 99%